The Validity and Practicality of the E-Book Science Model RADEC (Read-Answer-Discuss-Explain-Create) to Improve the 4C Skills of Students - Rissa Pramita; Yulkifli Yulkifli (Jurnal Penelitian Pendidikan IPA, 2023)
Quality human resources are the main goal of a nation's ability to compete. The demands of the 21st century also require quality human resources. Therefore, learning resources are needed that support students' 4C skills. The purpose of this research is to develop learning resources in the form of science e-books that have been tested for validity and practicality. The type of research used is research and development, using the ADDIE development model. In the ADDIE development model, there are five stages, including analysis, design, development, implementation, and evaluation. The validity of the Science E-Book uses the Aiken's V scale, and the practicality of the Science E-Book uses the Likert scale. Based on the results of the data analysis conducted, the validity and practicality results were obtained as follows. The results of e-book validity tests by experts were obtained at 0.88. The results of the teacher's practicality were obtained at 89.25%, and the results of the students' practicality were obtained at 88%. So it can be concluded that the RADEC model-based science e-book (Read-Answer-Discuss-Explain-Create) is valid and practical to use in science learning and to improve the 4C skills of junior high school students.